Ni-Cu / HDTMS-MX composite coating and preparation method thereof
By adding MXene sheets and cetyl trimethoxysilane protective film to the nickel-copper alloy plating layer, combined with pulse electrodeposition technology, the defects of nickel-copper plating during the electrodeposition process are solved, and its hydrophobicity and corrosion resistance are improved. , suitable for applications in complex environments.
Patent Information
- Application Number
- CN202411346058.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The pure nickel-copper alloy coating has defects such as pinholes and cracks caused by hydrogen evolution reaction during the electrodeposition process, and its wetting and self-cleaning properties are insufficient, making it difficult to maintain corrosion resistance in harsh environments.
Using Ni-Cu/HDTMS-MX composite plating, MXene sheet and cetyl trimethoxysilane protective film were added to the nickel-copper alloy plating, the two-dimensional layered structure and high elastic modulus of the MXene sheet were used to combine pulses. Electrodeposition technology and ultrasonic pretreatment form a plating layer with superhydrophobicity and high corrosion resistance.
It significantly improves the hydrophobicity, self-cleaning performance and corrosion resistance of nickel-copper plating, enhances the adaptability of the plating in complex environments, and provides better protection effects especially in seawater environments.
Smart Images

Figure CN119221070A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electroplating, and in particular to a Ni-Cu / HDTMS-MX composite coating and a preparation method thereof. Background Art
[0002] Nickel-copper based composite coating is a new type of composite coating with good corrosion resistance prepared by pulse electrodeposition technology. Since copper and nickel form a substitutional solid solution, nickel-copper coating has been widely used in harsh environments. Compared with other nickel-based coatings (such as nickel-tungsten coatings), nickel-copper coatings have excellent corrosion resistance due to the formation of a unique surface passivation film. However, pure nickel-copper alloy coatings will also have some defects during electrodeposition, such as pinholes and cracks produced by hydrogen evolution reactions. The presence of defects will reduce the service life of nickel-copper coatings. In addition, the wetting properties and self-cleaning properties of existing pure nickel-copper alloy coatings also need to be further improved. Summary of the invention
[0003] In view of the above problems, the present invention aims to provide a Ni-Cu / HDTMS-MX composite coating and a preparation method thereof.
[0004] The technical solution of the present invention is as follows:
[0005] On the one hand, a Ni-Cu / HDTMS-MX composite coating is provided, comprising a substrate, a filler and a surface protective film, wherein the substrate is a nickel-copper alloy coating, the filler is a MXene sheet, and the surface protective film is a hexadecyltrimethoxysilane protective film.
[0006] Preferably, the MXene sheet is obtained by the following steps: adding 0.5 g-2.0 g LiF to 20 mL-60 mL 7 mol / L-10 mol / L HCl solution, stirring for 30 min, and obtaining an etching solution with a concentration of 9 M; adding 0.5 g-5.0 g Ti 3 C 2 T x The reaction mixture is added to the etching solution and stirred at 40° C. for 24 hours to obtain a reaction solution; the reaction solution is washed and dried to obtain the MXene sheet.
[0007] Preferably, deionized water is used for washing until the pH value of the supernatant reaches 6.
[0008] Preferably, the mass ratio of the matrix to the filler is 1000:0.06-8.39.
[0009] On the other hand, a method for preparing a Ni-Cu / HDTMS-MX composite coating is also provided, comprising the following steps:
[0010] S1: obtaining a substrate and pretreating the substrate;
[0011] S2: preparing a Ni-Cu / MX composite plating solution including a nickel-copper plating solution and a MXene sheet, and performing ultrasonic pretreatment on the Ni-Cu / MX composite plating solution;
[0012] S3: placing the pretreated substrate into the pretreated Ni-Cu / MX composite plating solution for pulse electrodeposition to obtain an electrodeposited part;
[0013] S4: cleaning the electrodeposited plated part to obtain a Ni-Cu / MX composite coating;
[0014] S5: preparing a hexadecyltrimethoxysilane solution, and performing ultrasonic pretreatment on the hexadecyltrimethoxysilane solution;
[0015] S6: soaking the Ni-Cu / MX composite coating in the pretreated hexadecyltrimethoxysilane solution, and drying the solution after soaking to obtain the Ni-Cu / HDTMS-MX composite coating.
[0016] Preferably, in step S2, the Ni-Cu / MX composite plating solution comprises a nickel-copper plating solution and a MXene sheet in a mass ratio of 1000:0.06-8.39.
[0017] Preferably, the nickel-copper plating solution includes 100g / L-230g / L nickel sulfate, 30g / L-70g / L nickel chloride, 1.0g / L-5.0g / L copper sulfate, 50g / L-300g / L trisodium citrate, 10g / L-50g / L boric acid, and 0.1g / L-0.4g / L anionic surfactant.
[0018] Preferably, in step S3, when pulse electrodeposition is performed, the temperature is 20°C-80°C, the pH is 2±0.1-5±0.1, and the current density is 3A / dm 2 -9 A / dm 2 , the pulse frequency is 200Hz-800 Hz, the duty cycle is 10%-80%, the time is 10min-80min, and the magnetic stirring rate is 100rpm-600rpm.
[0019] Preferably, in step S5, the hexadecyltrimethoxysilane solution is prepared in a volume ratio of hexadecyltrimethoxysilane:pure water:anhydrous ethanol of 1:2:18.
[0020] Preferably, in step S6, the soaking is performed at 60° C. for 2 hours.
[0021] The beneficial effects of the present invention are:
[0022] The present invention uses the Ni-Cu coating as a matrix and the MXene sheet as a filler, and can fully utilize the two-dimensional layered structure of the MXene sheet and its high aspect ratio, high elastic modulus and other performance advantages, while giving play to the rough structural characteristics of the Ni-Cu / MXene surface. In addition, the coating achieves a super-hydrophobic effect through the hexadecyltrimethoxysilane protective film. In summary, the present invention can significantly improve the hydrophobicity, self-cleaning performance and corrosion resistance of the nickel-copper coating, enhance the adaptability of the coating to the actual application environment, and provide protection for the substrate in a complex seawater environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0024] Figure 1 TEM image and EDS spectrum of the MXene sheet in Example 1 of the present invention; wherein, Figure 1 (a) is a TEM image; Figure 1 (b)- Figure 1 (f) is the distribution diagram of each element of EDS;
[0025] Figure 2 The MXene sheet and Ti in Example 1 of the present invention 3 C 2 T x XRD spectrum of the material;
[0026] Figure 3 This is a particle size distribution diagram of the MXene sheet in Example 1 of the present invention;
[0027] Figure 4 The SEM images and partial magnified images of the coatings of Example 1 and Comparative Examples 1-2 of the present invention are shown; wherein: Figure 4 (a)-4(a 2 ) is a Ni-Cu plating layer; Figure 4 (b)-4(b 2 ) is Ni-Cu / MXene coating; Figure 4 (c)-4(c 2 ) is Ni-Cu / HDTMS-MX coating;
[0028] Figure 5 This is the EDS element mapping diagram of the Ni-Cu / HDTMS-MX coating in Example 1 of the present invention;
[0029] Figure 6 It is a schematic diagram of the three-dimensional profile and roughness results of each coating layer in Example 1 and Comparative Examples 1-2 of the present invention; wherein, Figure 6 (a)-6(c) are three-dimensional contour images of each coating; Figure 6 (d) is a schematic diagram of the Sq and Sa values of each coating;
[0030] Figure 7 The water contact angle diagram of each coating layer of Example 1 and Comparative Examples 1-2 of the present invention;
[0031] Figure 8 The water contact angle diagrams of the coatings of Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 of the present invention are shown;
[0032] Fig. 9 The water contact angle diagrams of the coatings of Example 1, Comparative Example 1, Comparative Example 5 and Comparative Example 6 of the present invention;
[0033] Fig.10 The water contact angle diagrams of the coatings of Example 1, Comparative Example 1, Comparative Example 7 and Comparative Example 8 of the present invention are shown;
[0034] Fig.11 It is a schematic diagram of the test results of the potentiodynamic polarization curves of each coating layer in Example 1 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0036] On the one hand, the present invention provides a Ni-Cu / HDTMS-MX composite coating, including a substrate, a filler and a surface protective film, wherein the substrate is a nickel-copper alloy coating, the filler is a MXene sheet, and the surface protective film is a hexadecyltrimethoxysilane protective film.
[0037] In a specific embodiment, the MXene sheet is obtained by the following steps: adding 0.5g-2.0g LiF to 20mL-60mL 7mol / L-10mol / L HCl solution, stirring for 30min, and obtaining an etching solution with a concentration of 9M; adding 0.5g-5.0g Ti 3 C 2T x The reaction mixture is added to the etching solution and stirred at 40° C. for 24 hours to obtain a reaction solution; the reaction solution is washed and dried to obtain the MXene sheet.
[0038] It should be noted that the use of etching to prepare MXene two-dimensional materials is a prior art, and the above embodiment is only a preferred mild etching method for MXene sheets in the present invention. In addition to this method, other methods in the prior art that can prepare MXene sheets can also be applied to the present invention.
[0039] In a specific embodiment, the washing is performed using deionized water until the pH value of the supernatant reaches 6.
[0040] In a specific embodiment, the mass ratio of the matrix to the filler is 1000:0.06-8.39.
[0041] On the other hand, the present invention also provides a method for preparing a Ni-Cu / HDTMS-MX composite coating, comprising the following steps:
[0042] S1: obtaining a substrate and pre-treating the substrate.
[0043] S2: preparing a Ni-Cu / MX composite plating solution including a nickel-copper plating solution and a MXene sheet, and performing ultrasonic pretreatment on the Ni-Cu / MX composite plating solution.
[0044] In a specific embodiment, the Ni-Cu / MX composite plating solution includes a nickel-copper plating solution and a MXene sheet in a mass ratio of 1000:0.06-8.39. Optionally, the nickel-copper plating solution includes 100g / L-230g / L nickel sulfate, 30g / L-70g / L nickel chloride, 1.0g / L-5.0g / L copper sulfate, 50g / L-300g / L trisodium citrate, 10g / L-50g / L boric acid, and 0.1g / L-0.4g / L anionic surfactant.
[0045] It should be noted that the nickel-copper plating solution in the above-mentioned embodiment is only a preferred nickel-copper plating solution formula of the present invention. The present invention mainly utilizes MXene sheets to modify the nickel-copper plating layer. In addition to the nickel-copper plating solution used in the above-mentioned embodiment, other nickel-copper plating solutions in the prior art can also be applied to the present invention.
[0046] S3: placing the pretreated substrate into the pretreated Ni-Cu / MX composite plating solution for pulse electrodeposition to obtain an electrodeposited part.
[0047] In a specific embodiment, when pulse electrodeposition is performed, the temperature is 20°C-80°C, the pH is 2±0.1-5±0.1, and the current density is 3A / dm2 -9 A / dm 2 , the pulse frequency is 200Hz-800 Hz, the duty cycle is 10%-80%, the time is 10min-80min, and the magnetic stirring rate is 100rpm-600rpm.
[0048] It should be noted that the use of pulse electrodeposition to obtain electrodeposited parts is a prior art. Those skilled in the art can adjust the pulse electrodeposition conditions according to the morphology and performance of the Ni-Cu / MX composite coating described in the present invention, and use pulse electrodeposition conditions under other parameters to obtain the Ni-Cu / MX composite coating described in the present invention.
[0049] S4: Cleaning the electrodeposited plated part to obtain a Ni-Cu / MX composite coating.
[0050] S5: preparing a hexadecyltrimethoxysilane solution, and performing ultrasonic pretreatment on the hexadecyltrimethoxysilane solution.
[0051] In a specific embodiment, the hexadecyltrimethoxysilane solution is prepared according to a volume ratio of hexadecyltrimethoxysilane:pure water:anhydrous ethanol of 1:2:18.
[0052] S6: soaking the Ni-Cu / MX composite coating in the pretreated hexadecyltrimethoxysilane solution, and drying the solution after soaking to obtain the Ni-Cu / HDTMS-MX composite coating.
[0053] In a specific embodiment, the immersion is performed at 60° C. for 2 hours.
[0054] Example 1
[0055] A Ni-Cu / HDTMS-MX composite coating is prepared by the following steps:
[0056] (1) Preparation of MXene sheets
[0057] First, 5.0 g LiF was added to 200 mL HCl solution and stirred for 30 min to obtain an etching solution with a concentration of 9 M. 2.0 g Ti 3 C 2 T x The reaction mixture was added into the etching solution and stirred at 40° C. for 24 h to obtain a reaction solution. The reaction solution was washed with deionized water until the pH value of the supernatant reached 6 to obtain a product. The product was dispersed in deionized water and ultrasonically dispersed for 40 min, and then freeze-dried to obtain the MXene sheet.
[0058] (2) Obtaining a substrate and pre-treating the substrate
[0059] In this embodiment, the substrate is J55 steel. When pre-treating the substrate, first, the J55 steel is ground and polished with metallurgical sandpaper to achieve a mirror effect; then, the steel is immersed in acetone and repeatedly rinsed with pure water and anhydrous ethanol to remove impurities, thereby removing excess organic matter; finally, the steel is activated with a 2.0 mol / L acetic acid solution.
[0060] (3) Preparing a Ni-Cu / MX composite plating solution and subjecting the Ni-Cu / MX composite plating solution to ultrasonic pretreatment
[0061] In this embodiment, the Ni-Cu / MX composite plating solution includes 170 g / L nickel sulfate, 45 g / L nickel chloride, 2.5 g / L copper sulfate, 105 g / L trisodium citrate, 35 g / L boric acid, 0.25 g / L sodium dodecyl sulfate, and 2.0 g / L MXene sheets.
[0062] In this embodiment, during the ultrasonic pretreatment, the Ni-Cu / MX composite plating solution is pretreated by a digital display water bath sonicator and a probe sonicator.
[0063] (4) Pulse electrodeposition to obtain electrodeposited parts
[0064] The pretreated substrate is placed in the pretreated Ni-Cu / MX composite plating solution for pulse electrodeposition. In this embodiment, the working anode is a graphite plate and the working cathode is activated carbon steel. The pulse electrodeposition temperature is 65°C, the pH is 4.1±0.2, and the current density is 6A / dm 2 , pulse frequency is 600 Hz, duty cycle is 40%, time is 30 min, and magnetic stirring rate is 400 rpm.
[0065] (5) Cleaning and silane-modifying the electrodeposited parts to obtain a Ni-Cu / HDTMS-MX composite coating
[0066] First, the electrodeposited parts are ultrasonically cleaned with ethanol and pure water in sequence to obtain a Ni-Cu / MX composite coating; then a hexadecyltrimethoxysilane solution is prepared according to a volume ratio of hexadecyltrimethoxysilane:pure water:anhydrous ethanol of 1:2:18, and ultrasonic pretreatment is performed for 30 minutes; the Ni-Cu / MX composite coating is placed in the pretreated hexadecyltrimethoxysilane solution, immersed at 60°C for 2 hours, and then dried in an oven at 60°C for 24 hours to obtain the Ni-Cu / HDTMS-MX composite coating.
[0067] Example 2
[0068] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 0.1 g / L.
[0069] Example 3
[0070] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 0.5 g / L.
[0071] Example 4
[0072] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 1.0 g / L.
[0073] Example 5
[0074] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 1.5 g / L.
[0075] Example 6
[0076] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 3.0 g / L.
[0077] Example 7
[0078] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 6.0 g / L.
[0079] Example 7
[0080] Different from Example 1, the amount of MXene flakes added in step (3) of this example is 10.0 g / L.
[0081] It should be noted that the above embodiments are only some embodiments of the present invention. By adopting the preparation method of the present invention and changing the parameters of the preparation method, such as changing the amount of MXene sheets added, changing the type and amount of reagents in the nickel-copper plating solution, changing the temperature and time and other parameters, the Ni-Cu / HDTMS-MX composite coating of the present invention can still be successfully prepared.
[0082] Comparative Example 1
[0083] Different from Example 1, step (1) is not performed in this comparative example, and the plating solution prepared in step (3) is directly a Ni-Cu plating solution. The Ni-Cu plating solution is different from the Ni-Cu / MX composite plating solution in that the MXene sheet is not included therein; the silane modification operation in step (5) is not performed in this comparative example, and the coating obtained in this comparative example is a Ni-Cu coating.
[0084] Comparative Example 2
[0085] Different from Example 1, the silane modification operation in step (5) is not performed in this comparative example, and the coating obtained in this comparative example is a Ni-Cu / MX coating.
[0086] Comparative Example 3
[0087] Different from Example 1, step (1) is not performed in this comparative example, and the plating solution configured in step (3) is a Ni-W plating solution, wherein the Ni-W plating solution comprises 15.8 g / L NiSO 4 6H 2 O, 46.2g / LNa 2 WO 4 ·2H 2 O, 14.7g / LNa 3 Cit, 15.2g / LNaBr, 26.7g / LNH 4 Cl, 1.0 g / L saccharin, 0.1 g / L SDS; the silane modification operation in step (5) was not performed in this comparative example, and the coating obtained in this comparative example was a Ni-W coating.
[0088] Comparative Example 4
[0089] Different from Example 1, the plating solution configured in step (3) of this comparative example is a Ni-W / MX plating solution, wherein the Ni-W / MX plating solution comprises 15.8 g / L NiSO 4 6H 2 O, 46.2g / LNa 2 WO 4 ·2H 2 O, 14.7g / LNa 3 Cit, 15.2g / LNaBr, 26.7g / LNH 4 Cl, 1.0 g / L saccharin, 0.1 g / L SDS, 2.0 g / L MXene sheet. The coating obtained in this comparative example is a Ni-W / HDTMS-MX coating.
[0090] Comparative Example 5
[0091] Different from Example 1, step (1) is not performed in this comparative example, and the filler in step (3) is GO instead of MXene. The coating obtained in this comparative example is a Ni-Cu / HDTMS-GO coating.
[0092] Comparative Example 6
[0093] Different from Example 1, the silane solution in step (5) of this comparative example is dodecyltrimethoxysilane (DTMS). The coating obtained in this comparative example is a Ni-Cu / DTMS-MX coating.
[0094] Comparative Example 7
[0095] Different from Example 1, in step (5), the hexadecyltrimethoxysilane solution is prepared with a ratio of hexadecyltrimethoxysilane to pure water of 1:20 and no anhydrous ethanol is added. The coating obtained in this comparative example is a Ni-Cu / 20-HDTMS-MX coating.
[0096] Comparative Example 8
[0097] Different from Example 1, in step (5), the hexadecyltrimethoxysilane solution is prepared with a ratio of hexadecyltrimethoxysilane to anhydrous ethanol of 1:20 and no pure water is added. The coating obtained in this comparative example is a Ni-Cu / 0-HDTMS-MX coating.
[0098] Test Example 1
[0099] The surface morphology, microstructure and particle size of the MXene sheets in Example 1 were analyzed using a transmission electron microscope (TEM, FEI Tecnai G2 F20), an X-ray diffractometer (XRD, PANalyticalX′Pert Pro) and a particle size analyzer (NanoBrook Omni). The results are as follows: Figure 1-3 shown.
[0100] from Figure 1 It can be seen that after etching and ultrasonic stripping, MXene appears as a single layer with a lateral size of about 1-3μm. The MXene flakes show clear transparency under the electron beam, indicating that it has a two-dimensional layered structure. EDS analysis shows that C and Ti elements are evenly distributed in MXene. In addition, the aluminum layer was successfully etched away in MXene, and the presence of aluminum was almost undetectable in the EDS analysis.
[0101] from Figure 2 It can be seen that Ti 3 C 2 T x The diffraction peaks mainly appear at 2θ=9.6, 19.1 and 38.8, corresponding to the (002), (004) and (104) crystal planes, respectively. After etching and ultrasonic stripping, the (002) peak of MXene shifted significantly to the left. The Bragg equation shows that the interlayer spacing of MXene has increased significantly. In addition, the XRD of the MXene sheet did not find any diffraction peaks related to the aluminum phase (104), which is consistent with the results of EDS analysis. These additional evidences confirm the successful synthesis of MXene.
[0102] from Figure 3 It can be seen that the average particle size of MXene sheets dispersed in aqueous solution is about 1 μm.
[0103] Test Example 2
[0104] The surface morphology and microstructure of the coating in Example 1 and the coatings in Comparative Examples 1 and 2 were analyzed using a scanning electron microscope (SEM, FESEM, Apreo S). The chemical composition of the coating in Example 1 was analyzed using an energy dispersive spectrometer (EDS, Aztec X-Max80). The results are as follows: Figure 4-5 shown.
[0105] from Figure 4 It can be seen that the surface of the Ni-Cu composite coating without MXene sheets has excellent flatness and the entire surface presents a velvety structure, which is consistent with previous reports. In contrast, the surface of the Ni-Cu / MXene composite coating is characterized by the presence of large and irregular clusters, which are randomly distributed on the coating surface. In addition, the undulations of the coating surface have also increased. Upon closer inspection, the clusters on the coating surface present micro / nano structures such as nodules. After the silane immersion process, the surface of the Ni-Cu / HDTMS-MX coating continues to present a rougher micro / nano structure. At the same time, it was observed that the coating surface was covered with a layer of organic matter (HDTMS).
[0106] like Figure 5 As shown, the EDS analysis results clearly show the presence of major elements, including nickel, copper and titanium, and the major elements are evenly distributed in the coating.
[0107] Test Example 3
[0108] The roughness of the coatings of Example 1, Comparative Example 1 and Comparative Example 2 was evaluated using a three-dimensional optical microscope (ContourGT-InMotion, USA). Figure 6 shown.
[0109] from Figure 6 It can be seen that the surface of the nickel-copper coating is smooth and uniform, while the surfaces of the Ni-Cu / MXene coating and the Ni-Cu / HDMTS-MX coating have obvious micro-nano rough structures. At the same time, the Ni-Cu / HDMTS-MX coating has higher Sq and Sa values.
[0110] Test Example 4
[0111] The contact angle test was conducted using a contact angle meter (SDC-350) to evaluate the wettability of pure water droplets on the coatings of Example 1 and Comparative Examples 1-6. The results are as follows: Figure 7-10 shown.
[0112] from Figure 7It can be seen that the pure Ni-Cu coating shows stronger hydrophilicity with a CA value of 83°. After adding MXene sheets, the surface CA of the Ni-Cu / MXene coating increased (reaching 119°). The contact angle of the Ni-Cu / HDTMS-MX coating reached 156°. The results show that the Ni-Cu / HDTMS-MX coating has significant hydrophobicity.
[0113] from Figure 8 It can be seen that the contact angle of the Ni-Cu / HDTMS-MX composite coating of the present invention is significantly higher than that of the Ni-W / HDTMS-MX coating. At the same time, it is obvious that the wetting performance improvement effect of MXene sheets and HDTMS on the Ni-Cu coating is higher than that on the Ni-W coating.
[0114] from Fig. 9 It can be seen that the CA of the Ni-Cu / HDTMS-GO coating and the Ni-Cu / DTMS-MX coating are 132° and 145°, respectively, which are significantly higher than the static water contact angle of the Ni-Cu coating, but lower than the static water contact angle of the Ni-Cu / HDTMS-MX coating (155°), and fail to achieve a superhydrophobic effect.
[0115] from Fig.10 It can be seen that the contact angle of the Ni-Cu / HDTMS-MX coating is higher than that of the other coatings, and the other coatings fail to achieve superhydrophobic effect. This shows that the appropriate ratio of the silane solution plays an important role in the wettability of the coating surface.
[0116] Test Example 5
[0117] The electrochemical response of the coatings of Example 1, Comparative Example 1 and Comparative Example 2 was detected by potentiodynamic scanning. The results are as follows: Fig.11 As shown. Fig.11 It can be seen that the self-corrosion potential of the Ni-Cu / HDTMS-MX coating is higher than that of the Ni-Cu coating and the Ni-Cu / MXene coating, which indicates that the corrosion resistance of the Ni-Cu / HDTMS-MX coating is better than that of the other two coatings.
[0118] It should be noted that the test data of the above embodiments are only the test data of the preferred embodiments of the present invention. Other Ni-Cu / HDTMS-MX coatings prepared by the preparation method of the present invention still have similar performance to Example 1, and can solve the crack problem of the Ni-Cu coating, obtain a dense and uniform micro- and nanostructure, and improve its wetting performance, self-cleaning performance, corrosion resistance, etc. compared with the Ni-Cu coating.
[0119] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A Ni-Cu / HDTMS-MX composite coating, characterized in that: It includes a substrate, a filler and a surface protection film, wherein the substrate is a nickel-copper alloy plating layer, the filler is a MXene sheet, and the surface protection film is a hexadecyltrimethoxysilane protection film.
2. The Ni-Cu / HDTMS-MX composite coating according to claim 1, characterized in that: The MXene sheet is obtained by the following steps: adding 0.5g-2.0g LiF to 20mL-60mL 7mol / L-10mol / L HCl solution, stirring for 30min, and obtaining an etching solution with a concentration of 9M; adding 0.5g-5.0g Ti3C2T x Add to the etching solution, stir at 40° C. for 24 hours to obtain a post-reaction solution; The post-reaction solution is washed and dried to obtain the MXene sheet.
3. The Ni-Cu / HDTMS-MX composite coating according to claim 2, characterized in that: When washing, deionized water is used for washing until the pH value of the supernatant reaches 6.
4. The Ni-Cu / HDTMS-MX composite coating according to claim 1, characterized in that: The mass ratio of the matrix to the filler is 1000:0.06-8.
39.
5. A method for preparing a Ni-Cu / HDTMS-MX composite coating, characterized in that: The following steps are involved: S1: obtaining a substrate and pretreating the substrate; S2: preparing a Ni-Cu / MX composite plating solution including a nickel-copper plating solution and a MXene sheet, and performing ultrasonic pretreatment on the Ni-Cu / MX composite plating solution; S3: placing the pretreated substrate into the pretreated Ni-Cu / MX composite plating solution for pulse electrodeposition to obtain an electrodeposited part; S4: cleaning the electrodeposited plated part to obtain a Ni-Cu / MX composite coating; S5: preparing a hexadecyltrimethoxysilane solution, and performing ultrasonic pretreatment on the hexadecyltrimethoxysilane solution; S6: soaking the Ni-Cu / MX composite coating in the pretreated hexadecyltrimethoxysilane solution, and drying the solution after soaking to obtain the Ni-Cu / HDTMS-MX composite coating.
6. The method for preparing the Ni-Cu / HDTMS-MX composite coating according to claim 5, characterized in that: In step S2, the Ni-Cu / MX composite plating solution includes a nickel-copper plating solution and a MXene sheet in a mass ratio of 1000:0.06-8.
39.
7. The method for preparing the Ni-Cu / HDTMS-MX composite coating according to claim 6, characterized in that: The nickel-copper plating solution includes 100 g / L-230 g / L of nickel sulfate, 30 g / L-70 g / L of nickel chloride, 1.0 g / L-5.0 g / L of copper sulfate, 50 g / L-300 g / L of trisodium citrate, 10 g / L-50 g / L of boric acid, and 0.1 g / L-0.4 g / L of anionic surfactant.
8. The method for preparing the Ni-Cu / HDTMS-MX composite coating according to claim 5, characterized in that: In step S3, when pulse electrodeposition is performed, the temperature is 20°C-80°C, the pH is 2±0.1-5±0.1, and the current density is 3A / dm 2 -9A / dm 2 , the pulse frequency is 200Hz-800 Hz, the duty cycle is 10%-80%, the time is 10min-80min, and the magnetic stirring rate is 100rpm-600rpm.
9. The method for preparing the Ni-Cu / HDTMS-MX composite coating according to claim 5, characterized in that: In step S5, the hexadecyltrimethoxysilane solution is prepared according to a volume ratio of hexadecyltrimethoxysilane:pure water:anhydrous ethanol of 1:2:
18.
10. The method for preparing the Ni-Cu / HDTMS-MX composite coating according to claim 5, characterized in that: In step S6, the immersion is performed at 60° C. for 2 hours.
